If the world were 100 people : a visual guide to our global village - McCann, Jacqueline (Crown Books for Young Readers, 2021)
"With almost 7.8 billion people sharing the earth, it can be a little hard to picture what the human race looks like all together. But if we could shrink the world down to just 100 people, what could we learn about the human race? What would we look like? Where and how would we all be living? This book answers all of these questions and more! Reliably sourced and deftly illustrated, If the World Were 100 People is the perfect starting point to understanding our world and becoming a global citizen. If we focus on just 100 people, it's easier to see what we have in common and what makes us unique. Then we can begin to appreciate each other and also ask what things we want to change in our world"--